Imatinib mesylate in the treatment of chronic myeloid leukemia: a local experience - Bee, P.C.; Gan, G.G.; Teh, A.; Haris, A.R. (Malaysian Medical Association, 2006)
This study was done to assess the overall response rate of imatinib mesylate in local patients with chronic myeloid leukaemia. A total of 69 patients were recruited with male/female ratio of 7:3. Of the 69 patients; 35% were in the chronic phase, 41% were in the accelerated phase, 17% were in blast crisis and the remaining 7% were after stem cell transplantation. Complete haematological response rates of patients in chronic phase, accelerated phase and blast crisis were 95.8%, 96.4% and 41.7% respectively. Thirty-eight percent of patients achieved complete cytogenetic response and 10% achieved partial cytogenetic response. The cytogenetic response rates were 80%, 41.7% and 18.2% in chronic, accelerated and blast crisis phase respectively (p < 0.005). Twenty-six percent of patients developed anaemia, 13% had neutropenia and 12% had thrombocytopenia after starting on treatment. In addition, 14% of patients developed peripheral oedema, 13% complained of musculoskeletal pain, 12% had gastrointestinal side effects which include nausea, vomiting and diarrhoea, 9% had grade 1 hepatotoxicity, 7% developed skin rashes and one patient had an abnormal renal function test. Patients taking 600mg or higher dosage of imatinib had more gastrointestinal side effects. Patients who weighed less than 60kg had a much higher risk of developing anaemia. Anaemia was a negative predictor of cytogenetic response. Presenting high white blood cell counts and absence of cytogenetic response were also negative predictors of survival. Overall survival was 87%. This was affected by the different phases of disease (chronic phase was better than accelerated and blast crisis) (p < 0.001). In conclusion, our local CML patients did well on treatment with imatinib.